Intestinal Macrophage Autophagy and its Pharmacological Application in Inflammatory Bowel Disease - Zheng, Yang; Yu, Yang; Chen, Xu-Feng; Yang, Sheng-Lan; Tang, Xiao-Long; Xiang, Zheng-Guo (Frontiers in Pharmacology, 2021)
Inflammatory bowel disease (IBD), comprised of Crohn's disease (CD) and ulcerative colitis (UC), is a group of chronic inflammatory disorders. IBD is regarded as a severe healthcare problem worldwide, with high morbidity and lethality. So far, despite of numerous studies on this issue, the specific mechanisms of IBD still remain unclarified and ideal treatments are not available for IBD. The intestinal mucosal barrier is vital for maintaining the function of the intestinal self-defensive system. Among all of the components, macrophage is an important one in the intestinal self-defensive system, normally protecting the gut against exotic invasion. However, the over-activation of macrophages in pathological conditions leads to the overwhelming induction of intestinal inflammatory and immune reaction, thus damaging the intestinal functions. Autophagy is an important catabolic mechanism. It has been proven to participate the regulation of various kinds of inflammation- and immune-related disorders via the regulation of inflammation in related cells. Here in this paper, we will review the role and mechanism of intestinal macrophage autophagy in IBD. In addition, several well-studied kinds of agents taking advantage of intestinal macrophage autophagy for the treatment of IBD will also be discussed. We aim to bring novel insights in the development of therapeutic strategies against IBD.